Multidimensional Model of Disability and Role Functioning in Rheumatoid Arthritis. Issue 12 (December 2015) - Ormseth, Sarah R.; Draper, Taylor L.; Irwin, Michael R.; Weisman, Michael H.; Aréchiga, Adam E.; Hartoonian, Narineh; Bui, Thuy; Nicassio, Perry M.
Abstract : Objective: To examine a model addressing the roles of rheumatoid arthritis (RA) disease burden, mood disturbance, and disability as determinants of impairments in role functioning. Methods: In a cross‐sectional design, 103 RA patients recruited from the community to participate in a clinical trial completed assessments of self‐assessed disease burden (total joint pain and disease activity), mood disturbance (Center for Epidemiological Studies Depression Scale depressed mood, somatic symptoms, lack of positive affect, and interpersonal problems), disability (Health Assessment Questionnaire disability index gross and fine motor), and role functioning (Short Form 36 health survey physical and social). Structural equation modeling (SEM) was used to examine direct and indirect mechanisms linking disease burden to role functioning. Results: SEM results indicated that the model had excellent fit: S‐Bχ 2 (30) = 38.59, P  = 0.135; comparative fit index = 0.977, standardized root mean residual = 0.062, and root mean square error of approximation = 0.053. Mediational analyses demonstrated that, while disease burden was associated with poor role functioning, its effects were jointly mediated by mood disturbance and disability. After the effects of mood disturbance and disability were taken into account, the effect of disease burden on role functioning was not significant. Conclusion: The results indicate that mood disturbance and disability may serve as important pathways through which RA disease burden affects role functioning. Future longitudinal research is suggested to replicate these findings and further explore the mediational mechanisms examined in this study.